2016
DOI: 10.1007/s00429-016-1282-1
|View full text |Cite
|
Sign up to set email alerts
|

Normal radial migration and lamination are maintained in dyslexia-susceptibility candidate gene homolog Kiaa0319 knockout mice

Abstract: Developmental dyslexia is a common disorder with a strong genetic component, but the underlying molecular mechanisms are still unknown. Several candidate dyslexia-susceptibility genes, including KIAA0319, DYX1C1, and DCDC2, have been identified in humans. RNA interference experiments targeting these genes in rat embryos have shown impairments in neuronal migration, suggesting that defects in radial cortical migration could be involved in the disease mechanism of dyslexia. Here we present the first characterisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 64 publications
(104 reference statements)
5
36
1
Order By: Relevance
“…Both KIAA0319 and KIAA0319L have been implicated in neuronal migration following knockdown experiments that specifically targeted neurons at the early stages of brain development using in utero shRNA in rats (11,(26)(27)(28)(29). However, knockout (KO) mouse models do not display any cortical abnormalities that could be explained by defective neuronal migration (30,31). Instead, the KO mice presented auditory system defects (31) in line with observations reported in adult rats that underwent KIAA0319 knock-down in utero (27,32,33).…”
Section: Introductionsupporting
confidence: 65%
“…Both KIAA0319 and KIAA0319L have been implicated in neuronal migration following knockdown experiments that specifically targeted neurons at the early stages of brain development using in utero shRNA in rats (11,(26)(27)(28)(29). However, knockout (KO) mouse models do not display any cortical abnormalities that could be explained by defective neuronal migration (30,31). Instead, the KO mice presented auditory system defects (31) in line with observations reported in adult rats that underwent KIAA0319 knock-down in utero (27,32,33).…”
Section: Introductionsupporting
confidence: 65%
“…However, examination of the brains of each of these KO mice revealed no abnormalities in the organisation of neurons in the neocortex. Kiaa0319 (Figure a; Martinez‐Garay et al., ), Dcdc2 (Wang et al., ), Dyx1c1 (Rendall, Tarkar, Contreras‐Mora, LoTurco, & Fitch, ) and Kiaa0319L (Guidi et al., ) displayed the normal layered structuring in the neocortex and no evidence of layer I ectopias, PVNH or other migration problems, contrary to what would be expected from the shRNA knockdown experiments conducted in rats. These studies are shown in Table .…”
Section: Functional Genetics and Neuronal Migrationmentioning
confidence: 92%
“…Doublecortin family members are known to have partially overlapping functions (Deuel et al., ; Koizumi, Tanaka, & Gleeson, ) and it is possible that the absence of migration defects in Dcdc2 KOs may be due to compensation by the Dcx gene. This could also explain the lack of defects observed at least in Kiaa0319 or Kiaa0319L KOs (Guidi et al., ; Martinez‐Garay et al., ). But this possibility was ruled out by examining double Kiaa0319; Kiaa0319L KO mice (Guidi et al., ), where both proteins are fully absent.…”
Section: Functional Genetics and Neuronal Migrationmentioning
confidence: 97%
See 1 more Smart Citation
“…Both KIAA0319 and KIAA0319L have been implicated in neuronal migration following knockdown experiments that specifically targeted neurons at the early stages of brain development using in utero shRNA in rats (Adler et al, ; Paracchini et al, ; Peschansky et al, ; Platt et al, ; Szalkowski et al, ). However, knockout (KO) mouse models do not display any cortical abnormalities that could be explained by defective neuronal migration (Guidi et al, ; Martinez‐Garay et al, ). Instead, the KO mice presented auditory system defects (Guidi et al, ) in line with observations reported in adult rats that underwent KIAA0319 knock‐down in utero (Centanni et al, ; Centanni et al, ; Szalkowski et al, ).…”
Section: Introductionmentioning
confidence: 99%